2014
DOI: 10.1158/1940-6207.capr-13-0426
|View full text |Cite
|
Sign up to set email alerts
|

miR-194 as a Predictor for Adenoma Recurrence in Patients with Advanced Colorectal Adenoma after Polypectomy

Abstract: microRNAs (miRNA) are promising predictors in colorectal cancer (CRC). We investigated whether miRNAs could predict adenoma recurrence in patients with advanced colorectal adenoma (ACRA) after polypectomy. miRNA expression profiling was performed by miRNA microarray to identify recurrencerelated miRNAs. Candidate miRNAs extracted from formalin-fixed paraffin-embedded blocks of patients with ACRA were measured using real-time PCR. Logistic regression analysis was conducted to investigate whether validated miRNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Furthermore, the authors noted that decreased levels of miR-194 expression was associated with tumor size, differentiation, and TNM stage (33). In a recent study, low expression of miR-194, adenoma size >2 cm, and >3 adenomas were shown to have independent risk factors for adenoma recurrence (34). In particular, it was found that in a 158-patient cohort, the sensitivity and specificity of miR-194 as a predictor were 71% and 78%, respectively, at a cut-off value of 0.13.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors noted that decreased levels of miR-194 expression was associated with tumor size, differentiation, and TNM stage (33). In a recent study, low expression of miR-194, adenoma size >2 cm, and >3 adenomas were shown to have independent risk factors for adenoma recurrence (34). In particular, it was found that in a 158-patient cohort, the sensitivity and specificity of miR-194 as a predictor were 71% and 78%, respectively, at a cut-off value of 0.13.…”
Section: Discussionmentioning
confidence: 99%
“…15 In CRC, miR-194 has been reported to be downregulated in colon tissues 16 and can predict adenoma recurrence. 17 Sundaram 18 found that miR-194 could promote angiogenesis and facilitate tissue repair by targeting thrombospondin-1. However, the functions and mechanisms of miR-194 involved in CRC are not fully elucidated and the therapeutic application of miR-194 has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-194 was frequently decreased in CRC, with this level closely associated with the overall survival of patients and obviously associated with tumor size, as well as the tumor node metastasis (TNM) stage that is involved with cell proliferation, colony formation, promoted G0/G1 arrest, and induced cell apoptosis through negative regulation of the MAP4K4/c-Jun/MDM2 or PDK1/AKT2/XIAP signaling pathway, and acts as an tumor inhibitor in CRC, but not related to lymphatic invasion and distant metastasis [ 65 , 66 ]. In addition, the low expression levels of miR-194 in patients, correlated with advanced colorectal adenoma (ACRA) after polypectomy, used independently as a better predictor for adenoma recurrence [ 67 ]. MiR-194 target genes display concordant expression profiles with oncogenic transcriptional regulator high-mobility group AT-hook 2 (HMGA2) involved in limiting cell proliferation and migration, reducing xenograft growth, attenuating cell migration, suppressing EMT, and promoting anticancer drug sensitivity in CRC [ 68 ].…”
Section: The Dual Role Of Mirna In Crcmentioning
confidence: 99%